Preparation and characterization of fat particles-in-water emulsions for the encapsulation of bioactive compounds using allanblackia seed fat and tween 20 and sodium alginate as emulsifying agents - Badu, Mercy (2016)
A thesis presented to The Department of Chemistry, College of Science, Kwame Nkrumah University of Science and Technology, in partial fulfilment for the award of the degree of Doctor of Philosophy in Chemistry, 2015